Comparison of consumption behaviors and development needs for the home meal replacement among Chinese college students studying abroad in Korea, Chinese college students in China, and Korean college students in Korea - Bae, Mi Ae; Park, So Hyun; Cheng, Siyao; Chang, Kyung Ja (Nutrition research and practice, 2021)
The consumption of home meal replacement (HMR) is increasing among college students in Korea and China. In particular, Chinese college students studying abroad in Korea (CSK) show changes in their dietary behavior after migration, and HMR consumption for meal substitution is also increasing. This study was conducted to compare the HMR consumption behaviors and HMR development needs of CSK, Chinese college students in China (CSC), and Korean college students in Korea (KSK).BACKGROUND/OBJECTIVESThe consumption of home meal replacement (HMR) is increasing among college students in Korea and China. In particular, Chinese college students studying abroad in Korea (CSK) show changes in their dietary behavior after migration, and HMR consumption for meal substitution is also increasing. This study was conducted to compare the HMR consumption behaviors and HMR development needs of CSK, Chinese college students in China (CSC), and Korean college students in Korea (KSK).The subjects were 570 college students (180 CSK, 200 CSC, and 190 KSK) who had experience of HMR consumption. Data were collected by face-to-face survey in 2019 and analyzed using SPSS 25.0.SUBJECTS/METHODSThe subjects were 570 college students (180 CSK, 200 CSC, and 190 KSK) who had experience of HMR consumption. Data were collected by face-to-face survey in 2019 and analyzed using SPSS 25.0.The majority of the subjects purchased HMR to 'saving time' and 'preventing meal skipping'. Average purchase price per HMR was about 5,000 won for the CSK and KSK, and about 3,000 won for the CSC. The most important attributes when selecting HMR for the CSK and CSC were hygiene, freshness, and taste in that order, while for the KSK were taste, price, and hygiene. Rice was preferred by the KSK while grilled and fried dishes were preferred by the CSK and CSC. In terms of development needs, dessert and meat-based side dishes were highest in all three groups. The preferred food materials for more than 50% of the subjects of all groups were beef, chicken, pork, shrimp, and squid, and spinach and Chinese cabbage in the CSK, and onion in the KSK.RESULTSThe majority of the subjects purchased HMR to 'saving time' and 'preventing meal skipping'. Average purchase price per HMR was about 5,000 won for the CSK and KSK, and about 3,000 won for the CSC. The most important attributes when selecting HMR for the CSK and CSC were hygiene, freshness, and taste in that order, while for the KSK were taste, price, and hygiene. Rice was preferred by the KSK while grilled and fried dishes were preferred by the CSK and CSC. In terms of development needs, dessert and meat-based side dishes were highest in all three groups. The preferred food materials for more than 50% of the subjects of all groups were beef, chicken, pork, shrimp, and squid, and spinach and Chinese cabbage in the CSK, and onion in the KSK.This study shows more effort is needed to develop the healthy customized HMR for college students studying in Korea and China, and that focuses are placed by CSK on hygiene and freshness, by CSC on meat side dishes, hygiene, and price, and by KSK on snacks (as meal substitutes), taste, and price.CONCLUSIONSThis study shows more effort is needed to develop the healthy customized HMR for college students studying in Korea and China, and that focuses are placed by CSK on hygiene and freshness, by CSC on meat side dishes, hygiene, and price, and by KSK on snacks (as meal substitutes), taste, and price.